Animal Models for Autoimmune Hepatitis: Are Current Models Good Enough? - Christen, Urs; Hintermann, Edith (Frontiers in Immunology, 2022)
Autoimmune liver diseases like autoimmune hepatitis, primary biliary cholangitis, primary sclerosing cholangitis, and IgG4-related cholangitis are chronic inflammatory diseases of the liver with an autoimmune background. The therapy of autoimmune hepatitis targets the autoreactive immune system and is largely dependent on the use of glucocorticoids and cytostatic drugs. In contrast, the treatment of cholestatic autoimmune liver diseases is restricted to the use of secondary or semi-synthetic bile acids, like ursodeoxycholic acid or obeticholic acid. Although the management of the disease using such drugs works well for the majority of patients, many individuals do not respond to standard therapy. In addition, chronic treatment with glucocorticoids results in well-known side effects. Further, the use of bile acids is a symptomatic therapy that has no direct immunomodulatory effect. Thus, there is still a lot of room for improvement. The use of animal models has facilitated to elucidate the pathogenesis of autoimmune liver diseases and many potential target structures for immunomodulatory therapies have been identified. In this review, we will focus on autoimmune hepatitis for which the first animal models have been established five decades ago, but still a precise treatment for autoimmune hepatitis, as obtainable for other autoimmune diseases such as rheumatoid arthritis or multiple sclerosis has yet to be introduced. Thus, the question arises if our animal models are too far from the patient reality and thus findings from the models cannot be reliably translated to the patient. Several factors might be involved in this discrepancy. There is first and foremost the genetic background and the inbred status of the animals that is different from human patients. Here the use of humanized animals, such as transgenic mice, might reduce some of the differences. However, there are other factors, such as housing conditions, nutrition, and the microbiome that might also play an important role. This review will predominantly focus on the current status of animal models for autoimmune hepatitis and the possible ways to overcome discrepancies between model and patient.